2014
DOI: 10.7861/clinmedicine.14-3-229
|View full text |Cite
|
Sign up to set email alerts
|

Licensing procedures and registration of medical doctors in the European Union

Abstract: The current proposals to update the European Union (EU) directive on professional qualifi cations will have potentially important implications for health professions. Yet those discussing it will struggle to fi nd basic information on key issues such as licensing and registration of physicians in different countries. A survey was conducted among national experts in 14 EU member states, supplemented by literature and independent expert review. The questionnaire covered fi ve components of licensing and registra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 5 publications
0
35
1
1
Order By: Relevance
“…Further, when representatives from 14 EU countries were surveyed, authors concluded that the systems of licensing and registration vary so much that it creates confusion and problems in the context of the free movement of doctors. In particular, there were large differences in how fitness to practise is conceptualised and some countries showed weaknesses in their systems that should identify doctors who are unfit to practise [35]. As well as IMGs, European graduates are more likely to experience difficulty in adapting to a very different healthcare context than the one in which they trained [21].…”
Section: Discussionmentioning
confidence: 99%
“…Further, when representatives from 14 EU countries were surveyed, authors concluded that the systems of licensing and registration vary so much that it creates confusion and problems in the context of the free movement of doctors. In particular, there were large differences in how fitness to practise is conceptualised and some countries showed weaknesses in their systems that should identify doctors who are unfit to practise [35]. As well as IMGs, European graduates are more likely to experience difficulty in adapting to a very different healthcare context than the one in which they trained [21].…”
Section: Discussionmentioning
confidence: 99%
“…Opponents of licensing examinations also suggest that easily testable learning outcomes become the focus of such examinations and that the competences needed more for actual practice are often missing from the blueprint (Neilson 2008;Noble 2008;Harden 2009). Their answer is for more job assessment, appraisal, and professional development to provide more accurate, up-to-date, and ongoing evidence of practitioner competence (Calnon 2006;Waldman & Truhlar 2013;Kovacs et al 2014). Neilson (2008) develops this argument: The standardisation of final, licensing, and fitness to practice examinations may make educationalists weep with joy, but there is no clear evidence that it makes for better doctors.…”
Section: Resultsmentioning
confidence: 99%
“…A third distinct group of countries exclusively involve international medical graduates (IMGs) who undergo an additional examination alongside an accreditation process, where they are required to provide evidence of language competence and validated documentation of their primary qualifications in order to practice in the new country. These include Australasia, parts of Europe (Sonderen et al 2009), including Sweden (Musoke 2012), and the United Kingdom (UK) (Kovacs et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, licensing and/or registration (again terms that have different meanings in different countries and both being used in different settings to explain the same processes) is indefi nite, whereas in others it is time limited and requires periodic relicensing and/or reregistration, 7 either by means of a simple reapplication or based on more formal requirements of demonstrating fi tness to practice. In both instances, professional misbehaviour and crimes can lead to a premature end of the license, although as we have shown elsewhere, the criteria for removal also vary markedly.…”
Section: Introductionmentioning
confidence: 99%
“…This is the second part in a series exploring professional standards across Europe and follows our work on licensing and registration processes. 7 …”
Section: Introductionmentioning
confidence: 99%